EKSISTENSI KELOMPOK KARAWITAN CAKRA BASKARA DI KABUPATEN KARANGANYAR - Mega Ayu Suryowati; I Nyoman Sukerna (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2017)
AbstractThe background to this research is the existence of a karawitan group that began in 2008 when its members were young children and has continued up to the time when they are already young men and women. The involvement of young people, the way in which performances are packaged, and the role of the community have all influenced the development of the Cakra Baskara karawitan group’s existence. The role of this group in the community and its ability to connect with the community are amongst the reasons for its continued existence. Various efforts have been made to preserve the existence of the Cakra Baskara karawitan group. Based on this background, the problems addressed in this research are the form of activities of the Cakra Baskara karawitan group and the factors that have caused the group to exist in its present form. A qualitative research method is used with an analytical descriptive approach. The writer uses Marx’s ideas about sociology, Sedyawati’s ideas of development. Using this method of approach, a picture was obtained about the existence of the Cakra Baskara karawitan group in the Karanganyar Regency and the factors that have caused the continued existence of this group.The involvement of young people in the Cakra Baskara karawitan group and the efforts (series of activities) that have been made to ensure the continued existence of the group include developments to the way in which performances are packaged in the supporting community. These activities include planning, organization, implementation, and management. The efforts to preserve the existence of the Cakra Baskara karawitan group through these activities are based on the motivation of members and stimulation from outside. The members’ motivation includes their desire to express their enjoyment of karawitan, to get together with people with a similar interest in the arts, and to increase their income. External stimulation which influences the continued existence of the Cakra Baskara karawitan group includes the support of the community and the community’s need for the presence of the Cakra Baskara karawitan group. Keywords: Existence, Cakra Baskara, Activities, Young People. AbstrakPenelitian ini dilatarbelakangi oleh keberadaan kelompok karawitan sejak tahun 2008 yang anggotanya masih anak-anak hingga tumbuh menjadi pemuda. Keterlibatan pemuda, kemasan pertunjukan yang disajikan dan peran masyarakat menyebabkan perkembangan terhadap eksitensi kelompok karawitan Cakra Baskara. Peran kelompok karawitan tersebut dalam masyarakat dan menyatu dengan masyarakat menjadikan kelompok tersebut tetap hidup. Upaya-upaya dilakukan untuk tetap mempertahankan eksistensi kelompok karawitan Cakra Baskara. Berdasarkan latar belakang tersebut, permasalahan yang diungkap adalah mengenai bentuk aktivitas kelompok karawitan Cakra Baskara serta faktor yang menyebabkan kelompok karawitan Cakra Baskara dapat menjadi bentuk seperti sekarang.Penelitian ini merupakan penelitian kualitatif dengan menggunakan metode deskriptik analitik. Penulis menggunakan pemikiran Marx mengenai sosiologi, Sedyawati mengenai perkembangan. Melalui pendekatan tersebut, didapatkan gambaran mengenai eksistensi kelompok karawitan Cakra Baskara di Kabupaten Karanganyar dan faktor yang menyebabkan kelompok tersebut tetap eksis.Keterlibatan pemuda di dalam kelompok karawitan Cakra Baskara dan upaya-upaya (serangkaian aktivitas) dilakukan untuk menjaga keeksisan kelompok karawitan tersebut melalui perkembangan kemasan pementasan di masyarakat pendukungnya. Aktivitas tersebut meliputi kegiatan perencanaan, pengorganisasian, pelaksanaan dan pengendalian. Upaya-upaya yang dilakukan untuk mempertahankan eksistensi kelompok karawitan Cakra Baskara melalui aktivitas yang didasari oleh motivasi anggota dan stimulasi dari luar. Motivasi anggota tersebut berupa keinginan untuk mengungkapkan rasa senang terhadap karawitan, berkumpul dengan orang-orang yang mempunyai minat sama dalam bidang seni, dan menambah penghasilan (keuangan). Stimulasi yang berpengaruh terhadap eksistensi karawitan Cakra Baskara tetap berupa dukungan masyarakat dan kebutuhan masyarakat akan kehidaran kelompok karawitan Cakra Baskara. Kata Kunci: Eksistensi, Cakra Baskara, Aktivitas, Pemuda